Interest rate caps in an economy with formal and informal credit markets - Jorge Pozo (Graduate Institute of International and Development Studies, 2022)
In this work, we aim to study the implications of the interest rate cap in an emerging economy. To do so we develop a two-period banking model with entrepreneurs that undertake risky projects and with formal and informal lenders. Entrepreneurs are heterogeneous in their level of net worth. We find that a cap on the lending interest rate excludes entrepreneurs with a low level of net worth, which in turn increases the participation of the informal credit market, but also might reduce bank markups increasing entrepreneurs' welfare. As a result, our model implies that the lower the market power of banks, the smaller the likelihood that the cap might have some positive impact on aggregate credit and investment.
Keywords: E5; G21; G23; 330; Interest rate cap; Informal credit market; monopoly banks